Allogeneic hematopoietic stem cell transplantation for patients with acute leukemia - Chen, Yan; Xu, Yajing; Fu, Gan; Liu, Yi; Peng, Jie; Fu, Bin; Yuan, Xiaoyu; Xin, Hongya; Zhu, Yan; He, Qun; Wu, Dengshu; Shu, Yigang; et al. (Chinese Journal of Cancer Research; Vol 25, No 4 (August 24, 2013): Chinese Journal of Cancer Research, 2013)
Objective: The purposes of this study were to assess the efficacy of allogeneic hematopoietic stem cell transplantation (HSCT) for acute leukemia (AL) and analyze the factors affecting the prognosis of these patients. Methods: The clinical and follow-up data of 93 AL patients (median age, 30 years) undergoing allogeneic HSCT in Xiangya Hospital over the past 12 years were collected, and the potential factors affecting the efficacy and prognosis of allogeneic HSCT patients were determined. Results: Hematopoietic reconstitution was achieved in 90 patients. At the last follow-up, the incidences of severe acute graft versus host disease (aGvHD) and extensive chronic GvHD (cGvHD) were 14.0% and 20.0%, the 3-year cumulative incidence of transplantation related mortality (TRM) and relapse rate were 16.8%±6.1% and 21.3%±6.7%, and the estimated 3-year overall survival (OS) and disease-free survival (DFS) of the patients were 64.6%±5.4% and 56.5%±5.5%, respectively. Univariate analysis indicated that age older than 40 years, HLA mismatch, and severe lung infection within the first 100 days after transplantation were risk factors for severe aGvHD, age older than 40 years, HLA mismatch, severe lung infection within the first 100 days after transplantation, and severe aGvHD were risk factors for TRM, high-risk AL and lack of cGvHD were risk factors for relapse (all P